Are Fungal Endophytes Merely Mycorrhizal Copycats? The Role of Fungal Endophytes in the Adaptation of Plants to Metal Toxicity - Domka, Agnieszka Małgorzata; Rozpaądek, Piotr; Turnau, Katarzyna (Frontiers in Microbiology, 2019)
The contamination of soil with toxic metals is a worldwide problem, resulting in the disruption of plant vegetation and subsequent crop production. Thus, remediation techniques for contaminated soil and water remain a constant interest of researchers. Phytoremediation, which utilizes plants to remove or stabilize contaminants, is perceived to be a promising strategy. However, phytoremediation’s use to date is limited because of constraints associated with such factors as slow plant growth rates or metal toxicity. Microbial-assisted phytoremediation serves as an alternative solution, since the impact of the microbial symbionts on plant growth and stress tolerance has frequently been described. Endophytic fungi occur in almost every plant in the natural environment and contribute to plant growth and tolerance to environmental stress conditions. Although this group of symbiotic fungi was found to form association with a wide range of hosts, including the non-mycorrhizal Brassicaceae metallophytes, their role in the response of plants to metal toxicity has not been thoroughly elucidated to date. This review summarizes the current knowledge regarding the role of endophytic fungi in the tolerance of plants to toxic metals and highlights the similarities and differences between this group of symbiotic fungi and mycorrhizal associations in terms of the survival of the plant during heavy metal stress.